Self-Confidence and Paranoia: An Experimental Study Using an Immersive Virtual Reality Social Situation. Issue 1 (11th November 2014) - Atherton, Stephanie; Antley, Angus; Evans, Nicole; Cernis, Emma; Lister, Rachel; Dunn, Graham; Slater, Mel; Freeman, Daniel
Abstract : Background: Paranoia may build directly upon negative thoughts about the self. There have been few direct experimental tests of this hypothesis.Aims: The aim of the study was to test the immediate effects of manipulating self-esteem in individuals vulnerable to paranoia.Method: A two condition cross-over experimental test was conducted. The participants were 26 males reporting paranoid ideation in the past month. Each participant experienced a neutral immersive virtual reality (VR) social environment twice. Before VR participants received a low self-confidence manipulation or a high self-confidence manipulation. The order of manipulation type was randomized. Paranoia about the VR avatars was assessed.Results: The low self-confidence manipulation, relative to the high self-confidence manipulation, led to significantly more negative social comparison in virtual reality and higher levels of paranoia.Conclusions: Level of self-confidence affects the occurrence of paranoia in vulnerable individuals. The clinical implication is that interventions designed to improve self-confidence may reduce persecutory ideation.